The Effect of HRM Practices and Self-Efficacy on The Performance of Academic Staff in Jordan: The Moderating Effect of Nepotism - Dehma Mofleh Qasem Al-Maraghi (Universiti Sains Islam Malaysia, 2024)
Matric: 4172480 (FKP)